Effect of the curcumin and piperine co-administration on the blood lipid levels and the cardiovascular risk: a systematic review (Research, Society and Development, 2021)
Some plant species show medicinal potential in atherosclerosis and other coronary diseases. Curcumin (CUR) is a yellow-colored phenolic compound from rhizomes of Curcuma longa L. that is mainly used as anti-inflammatory, antioxidant, and anticancer. Piperine (PIP) is an alkaloid from the fruits and the seeds of Piper nigrum L. and Piper longum L. It has several pharmacological activities, including the antioxidant and the immunomodulatory properties. PIP also increases the nutrients absorption. This review aims at investigating the effect of the CUR and PIP co-administration on the lipid profile and the cardiovascular events based on animal and human studies. This study was performed in the main scientific search bases. Among the 4,992 references found, 2,004 papers were initially chosen for the partial reading and 15 of them filled all the selection criteria for the entire reading. The CUR and PIP co-administration generally demonstrated positive effects on lipid profile in animals and humans by reducing total cholesterol, triglycerides, and LP(a) and by increasing HDL-c. In spite of no long-term clinical trial was carried out for investigating the effect of CUR and PIP co-administration on cardiovascular events, the reduction of glucose, AST, and ALP, and the increase of CAT and SOD were recorded as secondary serum markers to avoid the cardiovascular risk. Therefore, the studies usually report that co-administration of CUR and PIP shows efficacy for reducing serum lipids. The effect on preventing cardiovascular events by reducing the cardiovascular risk is lacking of direct evidence.